EVALUASI KEBIJAKAN PAUD PERMENDIKBUD NOMOR 30 - Warni Holiza; Yaswinda Yaswinda (Jurnal Inovasi Penelitian, 2022)
The family is the first educational institution in society, and parents are the main educators. Family is the first environment for children to grow and develop. Families in particular are parents who have an important role in the provision of education. Various surveys have shown that most parents spend their time working rather than interacting with their children. Family involvement in education is important and strategic in supporting the implementation of education to achieve national education goals. . family involvement in education requires a pattern of mutually supportive cooperation between education providers, families and communities. As a policy of the Minister of Education and Culture Number 30 of 2017 it really needs to be positively appreciated because it can maximize the role of the family in education. It's just that what needs to be clarified are the forms of activity in Article 6 of the Permendikbud. It is better if the form of family involvement in the implementation of education also pays attention to the interests of parents in the family. One of the reasons parents and guardians send their children to school is because they are not able to organize their children's education independently.